Algeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
Algeria's local corporate bond market provides a good basis for further diversifying the economy's financing channels. This study analyzes the nexus of bank financing of public enterprises in the ongoing national investment program (NIP) and also sets Algeria's local corporate bond market in a cross-country perspective. It develops options for developing local capital markets during the timeframe of the NIP, and considers improvements in some aspects of market functioning. The authorities have taken measures to help the banking system increase lending to public enterprises over the next few years.